Diversidade de mamíferos de médio e grande porte da região biogeográfica Tocantins-Maranhão - Ohana, José Abílio Barros (Museu Paraense Emílio Goeldi, 2023)
The Tocantins-Maranhão biogeographic unit is one of the most studied in the Amazon, with large samples of mammals deposited in museums. This region, however, still presents problems related to the taxonomy and geographical distribution of several species of this group. Some authors consider this area as a single operational biogeographic unit, although it is composed of two large segments, separated from each other by the Gurupi River. The aim of this study is to update the knowledge on the diversity of medium and large mammals in the study area, and to compare the diversity observed in each segment, verifying the suitability of dividing it into one or more distinct operational biogeographic units. The island of Marajó was also included as a third segment, as it presents faunal similarity with eastern Pará. A list was drawn up containing the species expected to occur in the region. To confirm the reliability of these records, a literature review was conducted and a survey of medium and large mammals deposited in the main Brazilian collections was carried out. Using the Jaccard index, the degree of faunal similarity between the segments of this region was analyzed. The list of expected taxa was composed of 55 species, distributed in 44 genera. Of these species, 53 (96.4%) were confirmed in collections, literature or by personal communication. There were no records for Atelocynus microtis, Tapirus terrestris and Inia geoffrensis in the collections, but T. terrestris and I. geoffrensis have already been recorded in the region through reliable direct observations. One species, Ozotoceros bezoarticus, was added to the list of mammals from the region. The results pointed out errors in the geographical distribution of some species, suggesting that considerable areas were inserted in the distributions of some taxa, described in the manuals of neotropical mammals consuItrated, only by means of extrapolation. Faunal similarity analysis indicated that Marajó Island is more similar to eastern Pará than to western Maranhão, but did not suggest the need to divide this biogeographic unit into two distinct ones. Of the 53 confirmed species, 12 (22.6%) are threatened with extinction, two of which are endemic (Cebus kaapori and Chiropotes satanas). The results presented here confirm the need for further studies of the medium and large mastofauna of the Tocantins-Maranhão biogeographic region. The occurrence of endemic and/or threatened species, in addition to the fact that this biogeographic unit is the most degraded in the Amazon, with great anthropic pressure, makes it urgent to take conservation measures, aiming at maintaining the diversity still existing in the place.